THE SOCIAL ECONOMICS OF UNIVERSAL HEALTH COVERAGE (BPJS KESEHATAN): A STUDY OF ITS IMPACT ON SOCIAL WELFARE AND HEALTHCARE EQUITY - Lefèvre, Pierre; Dubois, Marie; Moreau, Antoine (Cognitionis Civitatis et Politicae, 2025)
Indonesia’s implementation of Universal Health Coverage (UHC) through the BPJS Kesehatan program has been a significant step toward improving public access to healthcare. The program was designed to address long-standing issues of inequality and inaccessibility in healthcare services. However, its impact on social welfare and healthcare equity remains a topic of ongoing debate, particularly regarding its effectiveness in reducing healthcare disparities across different socio-economic groups. This study aims to analyze the social and economic impacts of BPJS Kesehatan, focusing on its contribution to social welfare and its role in promoting healthcare equity. Specifically, it examines whether the program has achieved its goals of improving healthcare access for marginalized populations and reducing financial barriers to healthcare. A mixed-methods approach was employed, combining quantitative analysis of healthcare utilization data and qualitative interviews with beneficiaries, healthcare providers, and policymakers. The study evaluates the financial sustainability of the program, its reach among low-income populations, and its effects on health outcomes. The results indicate that BPJS Kesehatan has increased healthcare access, particularly for low-income groups, but challenges remain in ensuring equitable service quality and financial sustainability. While healthcare utilization has risen, disparities in service delivery persist, particularly in rural areas. BPJS Kesehatan has made notable strides in improving healthcare access and equity, but further reforms are needed to address ongoing challenges in service quality, financial sustainability, and regional disparities.